Behavioral regulation by perineuronal nets in the prefrontal cortex of the CNTNAP2 mouse model of autism spectrum disorder - Gandhi, Tanya; Liu, Chin-Chi; Adeyelu, Tolulope T.; Canepa, Cade R.; Lee, Charles C. (Frontiers in Behavioral Neuroscience, 2023)
Autism spectrum disorders (ASDs) arise from altered development of the central nervous system, and manifest behaviorally as social interaction deficits and restricted and repetitive behaviors. Among the neural factors implicated in ASD, parvalbumin (PV) expressing interneurons have been implicated in the neuropathological and behavioral deficits in autism. In addition, perineuronal nets (PNNs), specialized extracellular matrix structures that enwrap the PV-expressing neurons, also may be altered, which compromises neuronal function and susceptibility to oxidative stress. In particular, the prefrontal cortex (PFC), which regulates several core autistic traits, relies on the normal organization of PNNs and PV-expressing cells, as well as other neural circuit elements. Consequently, we investigated whether PNNs and PV-expressing cells were altered in the PFC of the CNTNAP2 knockout mouse model of ASD and whether these contributed to core autistic-like behaviors in this model system. We observed an overexpression of PNNs, PV-expressing cells, and PNNs enwrapping PV-expressing cells in adult CNTNAP2 mice. Transient digestion of PNNs from the prefrontal cortex (PFC) by injection of chondroitinase ABC in CNTNAP2 mutant mice rescued some of the social interaction deficits, but not the restricted and repetitive behaviors. These findings suggest that the neurobiological regulation of PNNs and PVs in the PFC contribute to social interaction behaviors in neurological disorders including autism.